Innovative preparation route for uranium carbide using citric acid as a carbon source. Issue 15 (15th November 2016) - Salvato, D.; Vigier, J.-F.; Dieste Blanco, O.; Martel, L.; Luzzi, L.; Somers, J.; Tyrpekl, V.
Abstract: The preparation of uranium carbide (UC) by carbothermal reduction and its sintering into dense pellets by conventional means require high temperatures for long periods. We have developed a preparation route yielding fine UC powder with significantly increased sinterability. At first, a mixture of nanocrystalline UO2 embedded in amorphous carbon (nano-UO2 /C) was obtained by thermal decomposition of a gel containing solubilised uranyl nitrate and citric acid. Later, the nano-UO2 /C powder was treated in a conventional furnace or in a modified spark plasma sintering facility at elevated temperatures (≥1200 °C) in order to obtain uranium carbide powder. The effects of initial composition, temperature, gas/vacuum atmosphere and the overall reaction kinetics are reported. Graphical Abstract: